Effect of different recovery modes during resistance training with blood flow restriction on hormonal levels and performance in young men: a randomized controlled trial - Vahid Fekri-Kurabbaslou; Sara Shams; Sadegh Amani-Shalamzari (BMC, 2022)
Abstract Background Resistance training with blood flow restriction (BFR) results in hypertrophy, and its magnitude depends on various training variables. This study aimed to compare the long-term effect of passive recovery (PR) and active recovery (AR) during low-intensity resistance training with BFR on hormonal levels and performance in young men. Methods In the randomized clinical trial, 20 men were randomly divided into PR and AR groups during resistance training with BFR. The intervention consisted of six upper and lower body movements with 30% of one maximum repetition (1RM), three sessions per week for six weeks. Both groups wore pneumatic cuffs on the proximal part of thighs and arms. The cuff pressure was 60% of the calculated arterial blood occlusion and increased 10% every two weeks. The AR group performed seven repetitions in 30 s break between sets by one second for concentric and eccentric phases and two seconds rest, and the other group had passive rest. The blood samples and a series of performance tests were gathered before and after the intervention. A repeated measure ANOVA was used to analyze data. Results AR and PR interventions significantly improved the C-reactive protein (CRP) (− 38% vs. − 40%), Lactate dehydrogenase (LDH) (− 11% vs. − 3%), Sargent jump (9% vs. 10%), peak power (20% vs.18%), and average power (14% vs. 14%), upper 1RM (8% vs. 8%) and no significant differences were observed between groups. The AR intervention significantly increased growth hormone (GH) (423% vs. 151%, p = 0.03), lower body 1RM (18% vs. 11%) and muscle endurance (34% vs. 22% for the upper body, p = 0.02 and 32% vs. 24% for the lower body, p = 0.04) than the PR group. The PR intervention further increased the minimum power than the AR group (19% vs. 10%). There were no significant changes in testosterone (p = 0.79) and cortisol (p = 0.34) following interventions. Conclusion The findings indicated that by increasing muscle activation and higher metabolic load, AR during resistance training with BFR might cause more remarkable improvements in serum GH, muscle strength, and endurance. Thus, to gain further benefits, AR during training with BFR is recommended. Trial registration: IRCT20191207045644N1. Registration date: 14/03/2020. URL: https://www.irct.ir/search/result?query=IRCT20191207045644N1